Impact of neoadjuvant treatment on total mesorectal excision for ultra-low rectal cancers - Lim, Yon Kuei (BioMed Central, 2010)
BACKGROUND: This study reviewed the impact of pre-operative chemoradiotherapy or post-operative chemotherapy and/or radiotherapy on total mesorectal excision (TME) for ultralow rectal cancers that required either low anterior resection with peranal coloanal anastomosis or abdomino-perineal resection (APR). We examined surgical complications, local recurrence and survival. METHODS: Of the 1270 patients who underwent radical resection for rectal cancer from 1994 till 2007, 180 with tumors within 4 cm with either peranal coloanal anastomosis or APR were analyzed. Patients were compared in groups that had surgery only (Group A), pre-operative chemoradiotherapy (Group B), and post-operative therapy (Group C). RESULTS: There were 115 males and the mean age was 65.43 years (range 30-89). APR was performed in 134 patients while 46 had a sphincter-preserving resection with peranal coloanal anastomosis. The mean follow-up period was 52.98 months (range: 0.57 to 178.9). There were 69, 58 and 53 patients in Groups A, B, and C, respectively. Nine patients in Group B could go on to have sphincter-saving rectal resection. The overall peri-operative complication rate was 43.4% in Group A vs. 29.3% in Group B vs. 39.6% in Group C, respectively. The local recurrence rate was significantly lower in Group B (8.6.9% vs. 21.7% in Group A vs. 33.9% in Group C) p < 0.05. The 5-year cancer-specific survival rates for Group A was 49.3%, Group B was 69.9% and Group C was 38.8% (p = 0.14). CONCLUSION: Pre-operative chemoradiation in low rectal cancer is not associated with a higher incidence of peri-operative complications and its benefits may include reduction local recurrence.